2008
DOI: 10.1002/cyto.a.20659
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of CD4+CD25+ T regulatory cells for immunosuppressive therapy

Abstract: Immunosuppressants are powerful drugs, capable of triggering severe adverse effects. Hence, there is tremendous interest in replacing them with less-toxic agents. Adoptive therapy with CD25 1 CD4 1 T regulatory cells (Tregs) holds promise as an alternative to immunosuppressants. Tregs have been described as the most potent immunosuppressive cells in the human body. In a number of experimental models, they have been found to quench autoimmune diseases, maintain allogeneic transplants, and prevent allergic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 196 publications
4
71
0
Order By: Relevance
“…Much research effort has been devoted to implementing Treg-cell therapy in the clinic 1,2 and results of the first clinical trials have been recently reported. 3,4 Given their reduced circulating frequency (i.e., 5-10% of the CD4 + T cells) FOXP3 + Treg cells, to be of any therapeutic use in cell-therapy trials, need to be expanded ex vivo. The intrinsic reduced ability of Treg cells to proliferate in vitro can be reversed by potent stimulation through the T-cell receptor (TCR) in the presence of high doses of exogenous interleukin (IL)-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much research effort has been devoted to implementing Treg-cell therapy in the clinic 1,2 and results of the first clinical trials have been recently reported. 3,4 Given their reduced circulating frequency (i.e., 5-10% of the CD4 + T cells) FOXP3 + Treg cells, to be of any therapeutic use in cell-therapy trials, need to be expanded ex vivo. The intrinsic reduced ability of Treg cells to proliferate in vitro can be reversed by potent stimulation through the T-cell receptor (TCR) in the presence of high doses of exogenous interleukin (IL)-2.…”
Section: Introductionmentioning
confidence: 99%
“…5 Protocols for the expansion of human FOXP3 + Treg cells performed under conditions of good manufacturing practice (GMP) have been shown to be feasible. 3,[6][7][8] Importantly, these culture conditions are also highly advantageous for the expansion of effector CD25 + T cells, which may contaminate the starting peripheral FOXP3 + Treg cells. This obstacle can be bypassed by: (i) the use of cord blood Treg cells, 4 (ii) isolation of very pure peripheral Treg cells through flow-based cell sorters 3,9,10 or (iii) the addition of rapamycin to the culture, which preferentially inhibits proliferation of effector T cells while sparing Treg cells.…”
Section: Introductionmentioning
confidence: 99%
“…Murine CD3 (30)(31)(32). However, MACS separation can be hampered by contamination of T regs by T effector cells (33).…”
Section: Foxp3mentioning
confidence: 99%
“…There are two major obstacles hindering T reg therapeutic application: (1) inability to achieve stable, long-term donor-T reg engraftment; (2) difficulty in generating sufficient cell numbers required to inhibit undesired immune response(s), which also relates to T reg antigen (Ag) specificity. Data emerging from most recent T reg trials in T1D are demonstrating current limitations that rely solely on infusion of in vitro expanded T regs without any recipient manipulation in that expanded cells may have proinflammatory cells and limited ability to survive in nonlymphopenic host, leading to short lifespan in vivo (8)(9)(10)(11). Despite some success with T reg therapy in GVHD prevention (12)(13)(14), little is known about in vivo environment necessary for stable donor-T reg engraftment.…”
Section: Introductionmentioning
confidence: 99%